Supporting A-level sciences students to develop their revision strategies and exam technique - Bishop, D (2022)
This small-scale research and development study was designed to support of A-level chemistry students in developing effective revision strategies and exam techniques. The focus of this study was chosen in light of the lack of prior external examination experience due to the COVID-19 pandemic for the year 13 cohort (2021-22). This lack of exam experience and underperformance of students in mock examinations was a cause for concern for the science faculty and wider school leadership. A review of literature was carried out into the areas of learning strategies and students study skills, focussing on retrieval practice, self-regulation and metacognition to gauge a better understanding of the basis behind recall and application of knowledge. Using further literature practical strategies were identified for adaptation and use during the practitioner action research. Questionnaires were given to collaborating staff and A-level chemistry students to determine current practices prior to an intervention phase. A student focus group was used to delve deeper into their understanding of their perceptions of revision and exam preparation and their current experiences of exam preparation. Prior to any intervention, data showed an inconsistent picture of the delivery of revision strategies within lessons, and lack of explicit direction from teachers. Students demonstrated a mixed understanding of revision techniques with a narrow selection of passive, content-based strategies being predominantly favoured alongside mechanical use of practice exam questions. Using ideas obtained from the literature, exam board advance information, and teacher feedback, activities were designed to focus on key areas as well as being adaptable for students to use elsewhere in their exam preparation. On-going teacher feedback was collected throughout the intervention about the techniques delivered in lessons, perceptions of success and student engagement. Qualitative feedback from staff was positive and noted students throughout the intervention phase demonstrated excellent engagement using techniques introduced in sessions and increased communication with staff. Follow-up questionnaire data from students to identify changes in exam preparation habits showed an increase in the frequency and variation of strategies being used by students across all predicted attainment grades.